The Level Of Autonomy Of Muhammadiyah Junior High Schools In Sleman Regency Of Indonesia - Muhammad Hajar Dewantoro; Junanah Junanah; Mohamad Joko Susilo (International Journal of Pedagogy and Teacher Education, 2021)
The school autonomy is authority of schools without any intervention from other parties, ranging from management to curriculum, facilities and infrastructure, financing, implementation of teaching and learning process, teachers and staffs, and assessment. Thus, school is able to innovate in developing school branding, making it a top choice for the community. This study aimed to assesses school autonomy level, especially in Muhammadiyah schools. This survey using LCBT evaluation instrument model. The subject is Muhammadiyah Junior High School in Sleman Region, include: 254 person consist of 4 principals, 115 teachers and staffs, and 135 students grade 8 and 9. Data collecting technique using questionnaires, interview, and documentation. Data analysis using qualitative and quantitative descriptive technique. The results of study showed that SMP Muhammadiyah 1 Gamping has an autonomy score of 365.30 with strong category; SMP Muhammadiyah 1 Minggir has an autonomy score of 394.58 with very strong category; SMP Muhammadiyah 2 Kalasan has an autonomy score of 354.56 with strong category; and SMP Muhammadiyah 3 Depok has an autonomy score of 364.66 with strong category. Finally, it can be concluded that all of school are autonomy as can be realized with the branding of each school, outstanding achievements, school culture that has been ingrained in the heart all of school community, and high public interest.